A5.1 Abnormal Calcium Influx in T and B Lymphocytes from Systemic Lupus Erythematosus Patients is Related to STIM-1 Over-Expression. (25th February 2013) - Renaudineau, Yves; Mignen, Olivier; Fali, Tinhinane; Burgos, Miguel; Cornec, Divi; Jousse, Sandrine; Saraux, Alain; Pers, Jacques-Olivier
Abstract : Background and Objectives: Recently described, the molecule STIM1 (stromal interaction molecule 1) acts as a key mediator of calcium influx by controlling cell proliferation after antigen stimulation, Erk phosphorylation, cytokine production and apoptosis. Although STIM1 mutations have been associated with severe immunodeficiency, no study has focused on the STIM1 molecule in autoimmune diseases. Materials and Methods: T and B lymphocytes, purified by negative selection from peripheral blood of patients with systemic lupus erythematosus (SLE, n = 11), rheumatoid arthritis (RA, n = 7), primary Sjögren's syndrome (pSS, n = 11) and healthy controls (HC, n = 12) were tested by flow cytometry and Western blotting to determine the expression of STIM1. Video microscopy using specific probes has been used to assess intracellular calcium levels. Results: T cells from peripheral blood of HC express more STIM1 molecules (mean fluorescence intensity (MFI) 3.42 ± 0.13) than B cells (MFI 2.18 ± 0.20, P < 0.01). In B lymphocyte subpopulations, the expression of STIM1 is 2 times higher in CD24 high CD38 high transitional B cells (MFI 4.83 ± 0.63) compared with CD24 low CD38 low mature B cells (MFI 2.47 ± 0.15, P < 0.01) and CD24 high CD38 low memory B cells (MFI 3.64 ± 0.42, P < 0.05). The expression of STIM1 in T and B lymphocytes from patients with RA and pSS was similar to HC. An highest calcium influx and a constitutive Erk phosphorylation characterise T and B cells from SLE patients when compared with HC and disease controls. As suspected, STIM1 is over-expressed in SLE, when compared with HC and this expression is similar between T cells (MFI 8.70 ± 0.87) and B cells (MFI 9.00 ± 1.08). Within B cell subsets, STIM1 expression is 3.4 fold highest in transitional SLE B cells (MFI: 16.25 ± 2.18, P < 0.001) than in transitional HC B cells and 2.3 fold highest than in mature SLE B cells (MFI: 7.1 ± 1.53) and memory SLE B cells (MFI: 9.51 ± 2.01). Western blotting results confirm the highest expression of STIM1 in SLE. Transient transfection of STIM1-targeting siRNAs was shown to restore the calcium influx and decrease Erk phosphorylation. Of particular note, the associations of CpG/anti-IgM Ab and CpG/anti-CD40 Ab are effective to induce STIM1 expression. Finally, STIM1 level was not correlated with the SLE disease activity index (SLEDAI) and autoantibodies (ANA, anti-dsDNA, anti-SSA/Ro). Conclusions: These results suggest that the differential expression of STIM1 may be an important factor in the process of lymphocyte self-reactivity in SLE, which opens new pathophysiological and therapeutic perspectives.